Computation of air entrainment into a mixing pipe: An experimental and numerical analysis / Dipti Prasad Mishra and Subhash Chandra Paramanik - Mishra, Dipti Prasad; Paramanik, Subhash Chandra (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Computations of entrainment of air into a pipe were performed by placing an air jet at the bottom of the pipe. An experiment was performed with cylindrical mixing pipe having different diameter, length and jet location. A flow meter was used to measure the flow through the nozzle and velocity at the mixing pipe exit was measured by anemometer. CFD analyses were performed using Ansys-Fluent 16 to match the experimental results for exit velocity and amount of air sucked into the pipe. Further numerical investigations were performed for a mixing pipe with hot jet to estimate the amount of air entrained as a function pipe diameter, pipe length, nozzle protrusion and pipe shape. It was found from the numerical simulations there exists an optimum pipe length and nozzle protrusion for highest entrainment of air. Also a particular frustum shaped pipe could suck highest air compared to cylindrical shaped pipe.